Shopwindow perfume advertisement: reflection of multimodal cohesion in its structure - Nikiforova, Yevhenia; Popivniak, Olena; Galitska, Elizaveta (Current issues of Ukrainian linguistics: theory and practice, 2025)
This article examines the structural features that reflect two principal semiotic modes in the inner construction of a perfume advertisement, ultimately creating the overall semiotic structure of the ad. The advertisement, representing a pair of common brand perfumes, consists of five semi-individual panels. The constructional specification of this penta- fold paneled advertisement is intrinsically linked to its semiotic structure. The entire semiotic structure of the advertisement can be understood as comprising two independent modes: the verbal mode and the visual mode. Each mode is further subdivided into distinct components, and some components even include additional sub-components that contribute to the advertisement’s intricate design. The verbal semiotic mode includes essential components such as the naming complex, the logo, and the slogan. The naming complex itself is a multi-layered entity, comprising several sub-components, including the brandname, the individual name, the genitive name, and supplementary information that further clarifies the product’s identity. On the other hand, the visual semiotic mode is defined by its own set of components, namely the icon, colour, and space. The icon is made up of three sub-components: the perfume bottle, the model, and the background. The colour component is represented by a variety of sub- components, each contributing to the overall colour scheme that visually conveys the product’s appeal. Multimodal cohesion within this complex perfume advertisement is achieved through the reiteration of verbal and visual components, which are mirrored across the different panels. These reiterated components (sub-components) function as either hyper-integrants or hypo-integrants, creating a complex and densely interconnected net of repeated elements that together form the integrity of the advertisement. Furthermore, the advertisement’s five panels are spatially organised into three distinct groups based on their position within the layout: one central panel, two quasi-central panels, and two peripheral panels. This division not only reflects the structural symmetry of the advertisement but also enhances the emphasis placed on specific elements within the overall visual narrative. This study highlights the intricate ways in which verbal and visual components interact and support one another, creating a cohesive and compelling advertisement that appeals to both logical and emotional responses from the audience.